Exhaust gas purification materials and exhaust gas purification devices
The exhaust gas purification material with controlled noble metal particle size and distribution on metal oxide particles addresses durability issues, ensuring effective removal of harmful components at high temperatures.
Patent Information
- Application Number
- JP2021050112
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-03-24
AI Technical Summary
Noble metal particles used in exhaust gas purification systems lack durability at high temperatures, leading to decreased catalytic activity.
An exhaust gas purification material comprising metal oxide particles with noble metal particles supported on them, having an average particle size distribution of 1.5 to 18 nm and a standard deviation of less than 1.6 nm, which enhances catalytic performance under high temperature conditions.
The material maintains high efficiency in removing harmful components even after exposure to high temperatures by suppressing noble metal particle coarsening and maintaining a large specific surface area.
Smart Images

Figure 0007600808000003 
Figure 0007600808000001 
Figure 0007600808000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an exhaust gas purification material and an exhaust gas purification device. [Background technology]
[0002] Exhaust gases emitted from internal combustion engines used in automobiles and other vehicles contain harmful components such as carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NOx). Regulations on the emission of these harmful components are becoming stricter every year, and precious metals such as platinum (Pt), palladium (Pd), and rhodium (Rh) are used as catalysts to remove these harmful components.
[0003] On the other hand, from the viewpoint of resource risk, it is required to reduce the amount of precious metals used. In an exhaust gas purification device, it is known that one method of reducing the amount of precious metals used is to support the precious metals as fine particles on a carrier. For example, Patent Document 1 discloses a method for producing a catalyst, including a step of supporting precious metal particles on an oxide carrier to prepare a precious metal-supported catalyst, and a step of heat-treating the precious metal-supported catalyst in a reducing atmosphere to control the particle size of the precious metal within a predetermined range. Patent Document 2 discloses supported catalyst particles having oxide carrier particles and precious metal particles supported on the oxide carrier particles, the mass of the precious metal particles being 5 mass% or less based on the mass of the oxide carrier particles, the average particle size of the precious metal particles being 1.0 nm or more and 2.0 nm or less, and the standard deviation σ being 0.8 nm or less, as measured by a transmission electron microscope. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-147256 A [Patent Document 2] International Publication No. 2020 / 175142 Summary of the Invention [Problem to be solved by the invention]
[0005] The noble metal particles described in Patent Documents 1 and 2 do not have sufficient durability against high temperatures, and their catalytic activity may decrease under high temperature conditions.
[0006] Therefore, an object of the present invention is to provide an exhaust gas purification material and an exhaust gas purification device that can remove harmful components with high efficiency even after being exposed to high temperature conditions. [Means for solving the problem]
[0007] According to a first aspect of the present invention, there is provided an exhaust gas purification material, Metal oxide particles; Noble metal particles supported on the metal oxide particles; Including, The exhaust gas purification material is provided, in which the precious metal particles have a particle size distribution having an average of 1.5 to 18 nm and a standard deviation of less than 1.6 nm.
[0008] According to a second aspect of the present invention, A substrate; The exhaust gas purification material of the first embodiment disposed on the substrate; An exhaust gas purification device is provided, comprising: Effect of the Invention
[0009] The exhaust gas purifying material and exhaust gas purifying device of the present invention are capable of removing harmful components with high efficiency even after being exposed to high temperature conditions. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a graph showing the relationship between the average particle size distribution of the initial Rh particles in the pellets of Examples 1 to 4 and Comparative Examples 1 to 3 and NOx-T50. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present disclosure will be described with reference to the drawings as appropriate. In the drawings referred to in the following description, the same components or components having similar functions are given the same reference numerals, and repeated description may be omitted. In addition, the dimensional ratios of the drawings may differ from the actual ratios for convenience of explanation, and some components may be omitted from the drawings. In addition, in this application, a numerical range expressed using the symbol "~" includes the numerical values written before and after the symbol "~" as the lower limit and upper limit, respectively.
[0012] (1) Exhaust gas purification materials The exhaust gas purification material according to the embodiment includes metal oxide particles and precious metal particles supported on the metal oxide particles.
[0013] Examples of the metal oxide particles include particles of an oxide of at least one metal selected from the group consisting of metals in Groups 3, 4, and 13 of the periodic table and metals of the lanthanoid series. When the metal oxide particles contain oxides of two or more metals, the metal oxide particles may be a mixture of two or more metal oxides, a composite oxide containing two or more metals, or a mixture of at least one metal oxide and at least one composite oxide.
[0014] The metal oxide particles may be, for example, an oxide of at least one metal selected from the group consisting of scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), neodymium (Nd), samarium (Sm), europium (Eu), lutetium (Lu), titanium (Ti), zirconium (Zr) and aluminum (Al), preferably an oxide of at least one metal selected from the group consisting of Y, La, Ce, Ti, Zr and Al, more preferably at least one oxide selected from the group consisting of alumina (Al2O3), ceria (CeO2) and zirconia (ZrO2), and even more preferably a composite oxide containing alumina, ceria and zirconia, in particular a composite oxide containing alumina, ceria, zirconia, yttria (Y2O3), lanthana (La2O3), and neodymium oxide (Nd3O3).
[0015] The metal oxide particles may function as an OSC (Oxygen Storage Capacity) material that occludes oxygen in an oxygen-rich atmosphere and releases oxygen in an oxygen-deficient atmosphere.
[0016] The metal oxide particles may have any particle size depending on the purpose.
[0017] The precious metal particles supported on the metal oxide particles function as a catalyst for removing harmful components in exhaust gas. The precious metal particles may be particles of at least one metal selected from the group consisting of Pt, Pd, and Rh, and may be Rh particles.
[0018] The average of the particle size distribution of the precious metal particles is within the range of 1.5 to 18 nm. In general, the smaller the particle size of the precious metal particles, the larger the specific surface area of the precious metal particles, and therefore the higher the catalytic performance. However, precious metal particles with an excessively small particle size tend to become coarse due to aggregation under high temperature conditions, causing deterioration of catalytic performance. In this embodiment, the average of the particle size distribution of the precious metal particles is 1.5 nm or more, so that the coarsening of the precious metal particles under high temperature conditions is suppressed, and the deterioration of catalytic performance is suppressed. In addition, the average of the particle size distribution of the precious metal particles is 18 nm or less, so that the specific surface area of the precious metal particles is sufficiently large, and therefore the precious metal particles can exhibit high catalytic performance. The average of the particle size distribution of the precious metal particles may be within the range of 3 to 17 nm, or within the range of 4 to 14 nm.
[0019] In addition, the standard deviation of the particle size distribution of the precious metal particles is less than 1.6 nm. As the standard deviation of the particle size distribution of the precious metal particles is less than 1.6 nm, harmful components can be removed with high efficiency even after exposure to high temperature conditions, as shown in the examples described below. As the standard deviation of the particle size distribution of the precious metal particles is less than 1.6 nm, the number of coarse precious metal particles and the number of fine precious metal particles that are easily coarsened under high temperature conditions are reduced, so that the specific surface area of the precious metal particles after exposure to high temperature conditions is sufficiently large, and high catalytic performance can be exhibited. The standard deviation of the particle size distribution of the precious metal particles may be 1 nm or less.
[0020] In this application, the particle size distribution of the precious metal particles is a number-based particle size distribution obtained by measuring the projected area circle equivalent diameter of 50 or more precious metal particles based on an image obtained by a transmission electron microscope (TEM).
[0021] The amount of precious metal particles supported, i.e., the ratio of precious metal particles based on the total weight of metal oxide particles and precious metal particles, may be within the range of 0.01 to 2 wt%. When the ratio of precious metal particles is 0.01 wt% or more, a sufficient amount of precious metal particles is present, so that harmful components in exhaust gas can be removed. When the ratio of precious metal particles is 2 wt% or less, the precious metal particles are sufficiently loosely supported on the metal oxide particles, so that coarsening of the precious metal particles under high temperature conditions is suppressed. The ratio of precious metal particles based on the total weight of metal oxide particles and precious metal particles may be within the range of 0.2 to 1.8 wt%.
[0022] The method for supporting the precious metal particles on the metal oxide particles is not particularly limited. For example, the precious metal particles can be supported on the metal oxide particles by mixing the metal oxide particles, a dispersion of the precious metal particles, and water, drying the resulting mixture, and then calcining the mixture.
[0023] A dispersion of precious metal particles can be prepared, for example, by dissolving a chloride of a precious metal and polyvinylpyrrolidone in ethylene glycol, adding sodium hydroxide to the solution, and heating the solution. The average particle size of the precious metal particles supported on the metal oxide particles can be controlled by the amount of sodium hydroxide added.
[0024] The exhaust gas purification material according to the embodiment may further include other particles. Examples of the other particles include particles that function as an OSC material. For example, ceria, composite oxides containing ceria (e.g., ceria-zirconia composite oxide (CZ composite oxide), alumina-ceria-zirconia composite oxide (ACZ composite oxide)), and the like can function as the OSC material. In particular, CZ composite oxides are preferred because they have high oxygen storage capacity and are relatively inexpensive. Oxides obtained by further compounding CZ composite oxides with lanthana, yttria, and the like can also be used as the OSC material.
[0025] The exhaust gas purification material may be in a powder form, or may be molded into any shape such as pellets by press molding or the like.
[0026] (2) Exhaust gas purification equipment The exhaust gas purification material of the above embodiment can be used in an exhaust gas purification device. The exhaust gas purification device includes a substrate and an exhaust gas purification material disposed on the substrate. The exhaust gas purification material may be disposed on the substrate together with a binder, an additive, and the like.
[0027] The substrate is not particularly limited, but may be, for example, a monolith substrate having a honeycomb structure. The substrate may be formed of, for example, a ceramic material having high heat resistance such as cordierite (2MgO·2Al2O3·5SiO2), alumina, zirconia, silicon carbide, or a metal material made of a metal foil such as stainless steel. From the viewpoint of cost, the substrate is preferably made of cordierite.
[0028] When the substrate is a porous body having a plurality of pores, the exhaust gas purification material may be disposed on an inner surface that defines the pores of the substrate. In other words, in the present application, "disposed on the substrate" includes both being disposed on the outer surface of the substrate and being disposed on the inner surface of the substrate.
[0029] The exhaust gas purification material can be disposed on the substrate, for example, as follows. First, a slurry containing the exhaust gas purification material is prepared. The slurry may further contain a binder, an additive, etc. The properties of the slurry, for example, the viscosity, the particle size of the solid component, etc., may be appropriately adjusted. The prepared slurry is applied to a predetermined region of the substrate. For example, the predetermined region of the substrate is immersed in the slurry, and after a predetermined time has passed, the substrate is pulled up from the slurry, so that the slurry can be applied to the predetermined region of the substrate. Alternatively, the slurry may be poured into the substrate, and the slurry may be spread by blowing air with a blower, thereby applying the slurry to the substrate. Next, the slurry is dried and fired at a predetermined temperature and time. Thereby, the exhaust gas purification material is disposed on the substrate.
[0030] The exhaust gas purification device according to the embodiment can be applied to various vehicles equipped with an internal combustion engine.
[0031] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above-described embodiments, and various design modifications can be made without departing from the spirit of the present invention described in the claims. EXAMPLES
[0032] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.
[0033] <Example 1> (1) Sample preparation Polyvinylpyrrolidone and rhodium chloride were dissolved in ethylene glycol. Sodium hydroxide was added to the obtained solution. This solution was heated at 200° C. overnight. Thereby, a rhodium particle dispersion (Rh particle dispersion) was obtained.
[0034] The Rh particle dispersion and composite oxide particles of Al2O3, CeO2, ZrO2, La2O3, Y2O3, and Nd2O3 (hereinafter referred to as "ACZ particles" as appropriate. The weight ratio of each component in the ACZ particles was Al2O3: 30% by weight, CeO2: 20% by weight, ZrO2: 44% by weight, La2O3: 2% by weight, Y2O3: 2% by weight, and Nd2O3: 2% by weight) were added to distilled water, and the resulting mixture was heated and dried while stirring. The resulting particles were placed in a dryer maintained at 120°C for 2 hours to further remove moisture, and then heated to 500°C in an electric furnace for 2 hours.
[0035] The sintered particles were observed with a transmission electron microscope (TEM), and it was confirmed that Rh particles were supported on the ACZ particles. In addition, the particle size distribution of the Rh particles supported on the ACZ particles (initial Rh particles) was determined based on the TEM images. The average and standard deviation of the particle size distribution of the initial Rh particles are shown in Table 1. In addition, the weight ratio of the Rh particles in the sintered particles (i.e., the weight ratio of the Rh particles based on the total weight of the ACZ particles and the Rh particles) was as shown in Table 1.
[0036] The same weight of composite oxide particles of CeO2 and ZrO2 (hereinafter referred to as "CZ particles" as appropriate. The weight ratio of the components in the CZ particles was CeO2: 46% by weight, ZrO2: 54% by weight) was added to the fired particles, and the mixture was crushed and mixed in a mortar. 2 g of the obtained powder was weighed out and molded into pellets.
[0037] (2) Measurement of the average particle size of Rh particles after durability testing The pellets were heated to 1100°C and exposed to a stoichiometric (air-fuel ratio A / F=14.6) mixture and an oxygen-rich (lean: A / F>14.6) mixture alternately at a fixed time ratio of 1:1 for 5 hours. The average particle size of the Rh particles in the pellets was then determined by the carbon monoxide pulse method. The results are shown in Table 1.
[0038] (3) Exhaust gas purification performance evaluation After the durability test, the pellets were heated to 600°C while passing a gas having the composition shown in Table 2 through them at a flow rate of 15 L / min, and then cooled to 150°C after being maintained at that temperature for 5 minutes. Then, while continuing to pass the gas through the pellets, the pellets were heated to 600°C at a rate of 20°C / min, and the temperature of the pellets when 50% of the NOx in the gas was removed (denoted as "NOx-T50" as appropriate) was measured. The results were as shown in Table 1.
[0039] <Comparative Example 1> Except for using an aqueous rhodium nitrate solution instead of the Rh particle dispersion liquid, pellets were prepared in the same manner as in Example 1. The average and standard deviation of the particle size distribution of the initial Rh particles and the weight ratio of the Rh particles in the fired particles are shown in Table 1.
[0040] The average particle size of the Rh particles after the durability test of the pellets was measured, and the exhaust gas purification performance of the pellets was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0041] <Comparative Example 2> Pellets were prepared in the same manner as in Example 1, except that the Rh particle dispersion prepared in Example 1 was replaced with the Rh particle dispersion prepared as follows. 0.2 g of rhodium nitrate (III) was dissolved in 50 mL of ion-exchanged water to prepare an aqueous rhodium nitrate solution (pH 1.0). In addition, an aqueous tetraethylammonium hydroxide solution (pH 14) with a concentration of 175 g / L was prepared. A reactor (microreactor) having two flat plates as a clearance adjustment member was used to react the aqueous rhodium nitrate solution with the aqueous tetraethylammonium hydroxide solution. Specifically, the aqueous rhodium nitrate solution and the aqueous tetraethylammonium hydroxide solution were introduced into a reaction field with a clearance set to 10 μm at a molar ratio of tetraethylammonium hydroxide:rhodium nitrate=18:1 and reacted to prepare an Rh particle dispersion. The pH of the obtained Rh particle dispersion was 14.
[0042] The average and standard deviation of the particle size distribution of the initial Rh particles, and the weight ratio of the Rh particles in the fired particles are shown in Table 1.
[0043] The average particle size of the Rh particles after the durability test of the pellets was measured, and the exhaust gas purification performance of the pellets was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0044] <Example 2> Except for changing the amount of sodium hydroxide used in preparing the Rh particle dispersion, pellets were produced in the same manner as in Example 1. The average and standard deviation of the particle size distribution of the initial Rh particles, and the weight ratio of the Rh particles in the fired particles were as shown in Table 1.
[0045] The average particle size of the Rh particles after the durability test of the pellets was measured, and the exhaust gas purification performance of the pellets was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0046] <Examples 3 and 4, and Comparative Example 3> Except for changing the amount of sodium hydroxide used in preparing the Rh particle dispersion, pellets were produced in the same manner as in Example 1. The average and standard deviation of the particle size distribution of the initial Rh particles, and the weight ratio of the Rh particles in the fired particles were as shown in Table 1.
[0047] The exhaust gas purification performance of the pellets was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0048] <Comparative Example 4> A mixture of distilled water, Rh particle dispersion, and ACZ particles was prepared, dried, and sintered in the same manner as in Example 1. The obtained particles were heated to 900°C and exposed to a stoichiometric (air-fuel ratio A / F=14.6) air-fuel mixture and an oxygen-rich (lean: A / F>14.6) air-fuel mixture alternately at a constant time ratio of 1:1 for 5 hours.
[0049] The particles exposed to the gas mixture were then observed by TEM. The particle size distribution of the Rh particles supported on the ACZ particles (initial Rh particles) was determined based on the TEM images. The average and standard deviation of the particle size distribution of the initial Rh particles were as shown in Table 1. In addition, the weight ratio of the Rh particles in the particles (i.e., the weight ratio of the Rh particles based on the total weight of the ACZ particles and the Rh particles) was as shown in Table 1.
[0050] The particles exposed to the gas mixture were mixed with CZ particles of the same weight, crushed and mixed in a mortar. 2 g of the resulting powder was weighed out and molded into pellets.
[0051] The exhaust gas purification performance of the pellets was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0052] <Example 5> Except for changing the mixing ratio of the Rh particle dispersion and the ACZ particles, pellets were produced in the same manner as in Example 1. The average and standard deviation of the particle size distribution of the initial Rh particles, and the weight ratio of the Rh particles in the fired particles were as shown in Table 1.
[0053] The exhaust gas purification performance of the pellets was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0054] <Comparative Example 5> Except for changing the mixing ratio of the Rh particle dispersion and the ACZ particles, pellets were prepared in the same manner as in Comparative Example 2. The average and standard deviation of the particle size distribution of the initial Rh particles, and the weight ratio of the Rh particles in the fired particles are shown in Table 1.
[0055] The exhaust gas purification performance of the pellets was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0056] FIG. 1 shows the relationship between the average particle size distribution of the initial Rh particles and NOx-T50 in Examples 1 to 4 and Comparative Examples 1 to 3. The NOx-T50 in Examples 1 to 4, in which the average particle size distribution of the initial Rh particles was within the range of 1.5 to 18 nm, was lower than the NOx-T50 in Comparative Examples 1 to 3, indicating that the pellets in Examples 1 to 4 had higher NOx reduction performance. From the measurement results of the average particle size of the Rh particles after the durability test in Examples 1 and 2 and Comparative Examples 1 and 2 (see Table 1), it was shown that the coarsening of the Rh particles due to the durability test was suppressed in Examples 1 and 2, in which the average particle size distribution of the initial Rh particles was 1.5 nm or more, compared to Comparative Examples 1 and 2, in which the average particle size distribution of the initial Rh particles was less than 1.5 nm. Therefore, it is considered that the coarsening of the Rh particles was suppressed in Examples 1 to 4, in which the average particle size distribution of the initial Rh particles was 1.5 nm or more, and thus the reduction in the specific surface area of the Rh particles was suppressed, resulting in high NOx reduction performance. In addition, in Comparative Example 3, in which the average particle size distribution of the initial Rh particles exceeded 18 nm, the specific surface area of the Rh particles was small before the durability test, which is believed to have led to poor NOx reduction performance.
[0057] In Comparative Example 4, the average particle size distribution of the initial Rh particles was within the range of 1.5 to 18 nm, as in Examples 1 to 4, but the standard deviation of the particle size distribution of the initial Rh particles was 1.6 nm or more, which was larger than that of Examples 1 to 4 (see Table 1). This indicates that the pellets of Comparative Example 4 contained more fine Rh particles than the pellets of Examples 1 to 4. In Comparative Example 4, it is believed that the fine Rh particles were coarsened by the durability test, and therefore the specific surface area of the Rh particles after the durability test was smaller than that of Examples 1 to 4, and as a result, the NOx reduction performance was lower than that of Examples 1 to 4.
[0058] Similarly, the pellets of Example 5, in which the average particle size distribution of the initial Rh particles is within the range of 1.5 to 18 nm, showed a lower NOx-T50, i.e., a higher NOx reduction performance, than the pellets of Comparative Example 5, in which the average particle size distribution of the initial Rh particles is less than 1.5 nm. The difference in NOx reduction performance between Example 5 and Comparative Example 5 was smaller than the difference in NOx reduction performance between Example 1 and Comparative Example 2. This suggests the following. That is, when the weight ratio of Rh particles in the fired particles is within the range of 0.01 to 2 wt%, particularly 0.2 to 1.8 wt%, a sufficient NOx reduction performance improvement effect can be obtained by setting the average particle size distribution of the initial Rh particles to 1.5 nm or more. However, when the weight ratio of Rh particles in the fired particles is larger (for example, exceeding 2 wt%), there is a risk that a sufficient NOx reduction performance improvement effect cannot be obtained even if the average particle size distribution of the initial Rh particles is 1.5 nm or more.
[0059] [Table 1]
[0060] [Table 2]
Claims
1. An exhaust gas purification material, Metal oxide particles; Noble metal particles supported on the metal oxide particles; Including, the mean of the particle size distribution of the precious metal particles is 4 to 14 nm with a standard deviation of less than 1.6 nm; the metal oxide particles are composite oxide particles containing alumina, ceria, and zirconia; The exhaust gas purification material, wherein the precious metal particles are rhodium particles.
2. 2. The exhaust gas purification material according to claim 1, wherein the ratio of the precious metal particles is 0.01 to 2% by weight based on the total weight of the metal oxide particles and the precious metal particles.
3. An exhaust gas purification material as described in claim 1 or 2, wherein the average particle size distribution of the precious metal particles is 6.17 to 13.16 nm.
4. The exhaust gas purification material described in any one of claims 1 to 3, wherein the metal oxide particles are particles of a composite oxide containing alumina, ceria, zirconia, yttria, lanthana, and neodymium oxide.
5. A substrate; The exhaust gas purification material according to any one of claims 1 to 4, which is disposed on the substrate; An exhaust gas purification device comprising:
Citation Information
Patent Citations
Exhaust gas purification catalyst and method for producing it
CN105817223A
Platinum group metal (PGM) catalysts for automotive emissions treatment
CN107438483A
Novel PGM nanoparticles TWC catalysts for gasoline exhaust gas applications
EP3736037A1
Exhaust gas purification catalyst, and production method thereof
JP2016137445A
Method for producing catalyst and catalyst
JP2016147256A
